Functional properties of potato (Solanum tuberosum) starch and its chemical modification by acetylation - Vargas, G. (2016)
The potato (Solanum tuberosum) is an important source of starch which is underused in Peru, as are mainly imported potato starch, for has not been achieved yet, industrialization starch extraction is a success. This study aimed to obtain, characterize and modify chemically by acetylation, starch of a commercial potato variety, Unique. Extraction was performed with water and chemical modification was performed by acetylation using acetic anhydride at different levels (% v/w starch): 5, 10 y 15%. Native starch and modified starch were characterized: proximate composition, clear gel, apparent viscosity and stability to the freeze, also the percentage of acetyl groups (GA) was measured. The extraction yield was 16.5% and the apparent viscosity of native potato starch was 25000 mPas. Also starch modified with 15% acetylation for application in a cream ice cream because of their functional characteristics was selected. The apparent viscosity of gels modified starch potato was 5429 mPas. Acetyl groups varied from 0.44 to 1.26 % and degrees of substitution did not exceed levels recommended by FAO and JECFA. Starch AAc 15% showed the best functional profile for its application as stabilizer and thickener in refrigerated foods.